Functional state of mononuclear phagocytes in patients with multiple sclerosis carrying disease-associated HLA-DR polymorphism - Koliada, O. M.; Tynynyka, L. M.; Koliada, T. I.; Minukhin, V. V.; Nikolchenko, A. Y.; Taran, A. V.; Minukhina, D. V. (Regulatory Mechanisms in Biosystems, 2025)
One of the key factors in the pathogenesis of multiple sclerosis, which can affect the risk of its development, clinical manifestations and the nature of the course, is considered to be the polymorphism of disease-associated genes. The identification of genetic biomarkers in multiple sclerosis is the subject of current research in Europe, Asia, as well as in the United States and Canada, which are united in the International Multiple Sclerosis Genetics Consortium (IMSGC). The study included 137 patients with relapsing-remitting disease with haplotype AG, n = 137, and haplotype AA, n = 47; a group of patients with progressive multiple sclerosis with haplotype AG, n = 141, and haplotype AA, n = 17. Determination of the relative content of CD80, CD86 and PD-L1 positive peripheral blood monocytes was performed by immunofluorescence using PE-labeled monoclonal antibodies against CD14, FITC-labeled monoclonal antibodies against CD80, PE-Cy7-labeled monoclonal antibodies against CD86 and APC-labeled monoclonal antibodies against PD-L1 produced by EXBIO Praha, a. s. (Czech Republic). The content of cytokines (IFN-γ, IL-1β, IL-12, IL-10) in the supernatant of mononuclear macrophages was evaluated by enzyme-linked immunosorbent assay (ELISA). According to the results of the study, a method was proposed for identifying a genetic risk group for the development of multiple sclerosis by determining the SNP rs9271366 (AG) of the HLA-DRB1*1501-DQB1*0602 haplotype in individuals from the northeastern region of Ukraine . The minor allele was most often detected among patients with progressive PMS (89.2% vs. 10.8%), while among patients with relapsing-remitting disease the G allele was detected in 74.5% vs. 25.5%. The article deals with the antigen-presenting and cytokinesis properties of mononuclear phagocytes of patients with different types of multiple sclerosis depending on the presence of the disease-associated HLA-DR polymorphism. The level of CD86 expression was increased in all patients carrying the disease-associated allele, and the level of CD80 expression was increased only in heterozygous patients with progressive multiple sclerosis. The expression of PD-L1 molecules in patients with the disease-associated polymorphism was lower compared with both patients homozygous for the A-allele and the control group. The level of synthesis of cytokines IFN-γ, IL-1β, IL-12 in the supernatant of mononuclear macrophages of patients with progressive multiple sclerosis with the AG haplotype was more pronounced than in patients with relapsing-remitting multiple sclerosis with a disease-associated polymorphism with the AG haplotype, indicating the influence of genetic inheritance on the level of cytokine expression. It was found that the level of IL-10 in the supernatant of mononuclear macr o phages of patients with relapsing-remitting multiple sclerosis with the AG haplotype indicates a less pronounced effect of this interleukin on the compensation of proinflammatory imbalance.